Поняття політичної опозиції в контексті специфіки української політики - Манойло, Д.О.; Manoilo, D. (Харківський національний університет імені В. Н. Каразіна, 2013)
Детально розглядаються та аналізуються підходи до визначення поняття політичної опозиції, які наразі вживаються у вітчизняній і зарубіжній політології. Досліджуються специфічні риси української політики, які слід брати до уваги при визначенні політичної опозиції. У процесі дослідження було розгалужено такі поняття як „опозиція”, „парламентська опозиція”, та „політична опозиція”. Запропоновано підхід, що найбільш підходить до визначення політичної опозиції в контексті української політики. Approaches to the definition of the political opposition, which today are used in ukrainian and foreign political science, are reviewed and analyzed in detail in the article. Specific features of Ukrainian politics, which should be taken into account in determining the political opposition, are studied. During the study, concepts such as the „opposition”, „parliamentary opposition" and „political opposition" were branched. Approach that is most appropriate to the determination of the political opposition in the context of Ukrainian policy is proposed.
The definition of political opposition in the context of specificity of Ukrainian politics
Keywords: політична опозиція; парламентська опозиція; опозиція; ресурсний підхід; інституційний підхід; the political opposition; the parliamentary opposition; the opposition; the resourcebased approach; the institutional approach